Pemanfaatan Quizizz Sebagai Media Pembelajaran Berbasis Game Pada Masa Pandemi Covid-19 - Destri Sambara Sitorus; Tri Nugroho Budi Santoso (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2022)
The Covid-19 pandemic has hit all countries in the world has had an impact on many sectors, including the education sector. Teaching and learning activities are transferred to a virtual face room. Online learning is carried out with the help of technology, one of those is quizizz which is a game-based learning media. This research is a qualitative research that aims to obtain information about the use of the Quizizz application in economic learning. The research subjects were high school and vocational high school students in Salatiga City, Boyolali Regency, and Semarang Regency. The results showed that the use of quizizz had a positive impact on students. Quizizz helped them to better understand the material, did not make them bored in learning, made them more enthusiastic, focused, and active in learning, relaxes when they were bored, makes students think critically, competitively, and broadly.